Study of nuclear cataract progression using the National Eye Institute Scheimpflug system. - Datiles, M B (1995)
AIMS--A study was conducted to determine the capability of the recently developed National Eye Institute (NEI) Scheimpflug cataract imaging system in detecting changes in the nuclear region of the lens over a 1 year period. METHODS--Twenty five eyes with pure nuclear cataracts with mean nuclear densities < or = 0.30 optical density units (ODU) as well as 30 normal control eyes were each examined at baseline and 12 months later. Computerised densitometry using the NEI Scheimpflug cataract imaging system was performed. Clinical grading of the lenses was also done using the Lens Opacities Classification System II (LOCS II). For densitometry, a change of plus or minus 0.023 ODU (the 99% range) in mean density in the nuclear area was considered a progression or regression at 1 year. RESULTS--Using the Scheimpflug densitometry, 14 of the 25 cataractous eyes showed significant progression at 1 year. In the normal control group, only three of the 30 eyes showed significant progression. In contrast, using the LOCS II clinical grading, only two of the 25 cataractous eyes showed a one step increase, two of the 30 controls progressed at 1 year, and none regressed. There was no significant difference in visual acuity. CONCLUSION--This study suggests the value of the NEI Scheimpflug cataract imaging system in detecting nuclear change within 1 year. However, clinically significant changes may require longer follow up periods. These data will be useful in planning future longitudinal studies of nuclear cataracts, such as for clinical trials of anticataract drugs.